EFFECT OF ORGANIC AMENDMENT ON SOIL COMPACTION UNDER OPEN GRAZING SYSTEM - Adigun, Habeeb Adekunle; Lawal, Ahmad; Aliyu, Muzzamil; Sheu, Abdulrahman Umar; Noma, Danjuma (FUDMA JOURNAL OF SCIENCES, 2026)
The system of open grazing common in Northern Nigeria, leaves traces of soil compaction along the route of grazing. This trampling by livestock compact agricultural soil which leads to degradation.  This research investigated the effectiveness of organic amendments in mitigating soil compaction under open grazing conditions in Birnin Kebbi, Nigeria. A split-plot experiment compared compost, farmyard manure, and a control over six months (at zero month, after three months, and after six months). Results obtained showed that organic amendments significantly reduced bulk density (1.87–1.57 g cm⁻³) and penetration resistance (0.41–0.35 MPa), while increasing porosity (29.31%–40.63%), aggregate stability (39.45%–68.85%), and soil moisture retention (3.97–6.40%). Compost consistently produced the greatest improvements, with optimal effects observed after six months. Structural properties such as bulk density, porosity, and aggregate stability exhibited strong interaction effects between amendment type and observation time, indicating progressive soil improvement due to organic matter decomposition. The findings of the research demonstrate that organic amendments, particularly compost, enhance soil resilience to trampling by improving its physical structure and hydraulic properties. This highlights the incorporation of amendment potential as sustainable management strategies for restoring soil quality and productivity in lands under open grazing system.
Keywords: Observation time, Soil compaction, Bulk density, Penetration resistance and Porosity